Characterisation of CYP2C8, CYP2C9 and CYP2C19 polymorphisms in a Ghanaian population - Kudzi, William; Dodoo, Alexander NO; Mills, Jeremy J (My University, 2009)
Abstract Background Genetic influences on drug efficacy and tolerability are now widely known. Pharmacogenetics has thus become an expanding field with great potential for improving drug efficacy and reducing toxicity. Many pharmacologically-relevant polymorphisms do show variability among different populations. Knowledge of allelic frequency distribution within specified populations can be useful in explaining therapeutic failures, identifying potential risk groups for adverse drug reactions (ADRs) and optimising doses for therapeutic efficacy. We sought to determine the prevalence of clinically relevant Cytochrome P450 (CYP) 2C8, CYP2C9, and CYP2C19 variants in Ghanaians. We compared the data with other ethnic groups and further investigated intra country differences within the Ghanaian population to determine its value to pharmacogenetics studies. Methods RFLP assays were used to genotype CYP2C8 (*2, *3, *4) variant alleles in 204 unrelated Ghanaians. CYP2C9*2 and CYP2C19 (*2 and *3) variants were determined by single-tube tetra-primer assays while CYP2C9 (*3, *4, *5 and *11) variants were assessed by direct sequencing. Results Allelic frequencies were obtained for CYP2C8*2 (17%), CYP2C8*3 (0%), CYP2C8*4 (0%), CYP2C9*2 (0%), CYP2C9*3 (0%), CYP2C9*4 (0%), CYP2C9*5 (0%), CYP2C9*11 (2%), CYP2C19*2 (6%) and CYP2C19*3 (0%). Conclusion Allele frequency distributions for CYP2C8, CYP2C9 and CYP2C19 among the Ghanaian population are comparable to other African ethnic groups but significantly differ from Caucasian and Asian populations. Variant allele frequencies for CYP2C9 and CYP2C19 are reported for the first time among indigenous Ghanaian population.